Correlation between Glycated Hemoglobin Levels and Knowledge, Attitude, and Practice of Type 2 Diabetic Patients Attending Primary Health Care Centers in Dubai Health Authority - Hind Al Razooqi; Bashayer AlNajjar; Ebrahim AlShamsi; Kaltham Ibrahim; Wadeia Sharief; Hamda Khansaheb; Marwan Zidan (Dubai Medical Journal)
Introduction: Type 2 diabetes mellitus (DM) is not only one of the fastest-growing health problems in the world but also a burden that is reaching to epidemic proportion worldwide. Knowledge, attitude, and practice (KAP) significantly impact the outcome of self-management in patients with diabetes, yet the association between KAP of type 2 diabetes and the combined control of the glycated hemoglobin (HbA1c) level to date remains uncertain due to lack in the number of studies. This study aimed to find the correlation between the KAP of type 2 diabetes and HbA1c levels in patients attending primary health care centers (PHCs) in Dubai. Methods: This cross-sectional study was conducted by a face-to-face questionnaire in patients with type 2 diabetes who visited PHCs in Dubai. We included ten PHCs. Participants were 292 females and males aged 18 years and above. The revised Michigan diabetes KAP scales on type 2 DM patients was used to assess the KAP. Results: The mean knowledge percent score of type 2 diabetic patients was 75.6%. Yet there is no evidence that it correlates with HbA1c levels. The correlation coefficient between the knowledge score and HbA1c is 0.032 (95% CI [−0.096 to 0.159], p value = 0.628). Factors that affected HbA1c levels were the level of education, marital status, and duration of diabetes (p value: 0.029, 0.003, and 0.006, respectively). For the level of education, the illiterate group had the highest HbA1c (median: 7.5 [5.6–14]), while the University group had the lowest HbA1c (median: 6.75 [4.8–12.8]). Also, widowed participants had the highest HbA1c (median: 7.5 [6.5–14]), while married participants had the lowest HbA1c (median: 6.9 [4.8–12.8]). Finally, participants with a duration of diabetes more than 20 years had the highest HbA1c (median: 7.8 [5.8–14]), and those who had a duration of diabetes for 6–10 years (median: 6.9 [5.1–13.1]) and those with a duration of diabetes 1–5 years (median: 6.9 [5.3–12.8]) had the lowest HbA1c. Conclusion: Although the study shows that type 2 diabetic patients attending primary health centers in Dubai had relatively adequate scores in knowledge, this could be further improved by implementing continuous awareness programs of type 2 DM to improve their understanding, compliance, and management, thereby reducing the severity of disease.